FAKTOR-FAKTOR YANG BERPENGARUH PADA INTENSITAS PERILAKU DALAM PENGGUNAAN E-FILING OLEH WAJIB PAJAK ORANG PRIBADI - Dharma, I Wayan Maha Hredaya; Noviari, Naniek (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
E-filing users are more than 7 million in 2016. Number of users also show significant growth in 2014 and 2015 each about 1 million and 2 million users. The intensity of taxpayer’s behavior in using e-filing is taxpayer willingness to use e-filing and reuse it in the future. Knowing the factors that have influence on the intensity of this behavior is an important thing. This study conducted on individual taxpayers in the East Denpasar Small Tax Office. Number of samples examined in this researchwere 100 individual taxpayers. Data collected through questionnaires by incidental sampling technique. Analysis technique used was multiple linear regression analysis. Based on results of the research the conclusion is perceived usefulness, perceived ease to use, security and privacy, as well as readiness of taxpayer technology information partially have positive influence on the intensity of individual taxpayer’s behavior in using e-filing in East Denpasar Small Tax Office.
Keywords: the intensity of behavior, e-filing, individual taxpayer